2021
DOI: 10.1080/22221751.2021.1902753
|View full text |Cite
|
Sign up to set email alerts
|

Experimental re-infected cats do not transmit SARS-CoV-2

Abstract: SARS-CoV-2 is the causative agent of COVID-19 and responsible for the current global pandemic. We and others have previously demonstrated that cats are susceptible to SARS-CoV-2 infection and can efficiently transmit the virus to naïve cats. Here, we address whether cats previously exposed to SARS-CoV-2 can be re-infected with SARS-CoV-2. In two independent studies, SARS-CoV-2-infected cats were re-challenged with SARS-CoV-2 at 21 days post primary challenge (DPC) and necropsies performed at 4, 7 and 14 days p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 43 publications
2
53
1
1
Order By: Relevance
“…The case described here presents striking similarities (clinical, virological and pathological) with severe cases of COVID-19 in humans [ 33 , 35 ]. Clinically the animal presented severe progressive respiratory distress for 5–6 days and was non-responsive to supportive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The case described here presents striking similarities (clinical, virological and pathological) with severe cases of COVID-19 in humans [ 33 , 35 ]. Clinically the animal presented severe progressive respiratory distress for 5–6 days and was non-responsive to supportive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The full set of signature mutations on and around the RBD of the S protein, as well as mutations in other genomic regions of SARS-CoV-2 VOC, contribute to the characteristics of each variant, and particular attention has been directed towards the roles of amino acid residues located on the S protein's RBD, due to its direct interaction with ACE2. To understand the effects of key mutations of the Alpha, Beta, and Delta VOC, we tested respective pseudotyped viruses in virus neutralization assays with convalescent human and cat (from a challenge study with the SARS-CoV-2 USA-WA1/2020 strain [72]) sera, and hyperimmune rabbit sera (immunized with baculovirus-expressed prototype parental S protein). Substitution N501Y is found in Alpha, Beta and Gamma VOC and reported to have an increased binding efficacy to human ACE2 [73].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown successful infection of cats with SARS-CoV-2 via intranasal (1–3.05 × 10 5 PFU) and/or intra-oral routes (5 × 10 5 TCID 50 / mL ) and have confirmed cat-to-cat transmission through both respiratory droplets and aerosolization [ 16 , 26 , 27 , 28 ]. However, these studies failed to produce clinical signs in infected cats, and evidence of lower respiratory pathology mirroring severe COVID-19 in humans was not observed [ 16 , 26 , 27 , 28 ], potentially due to concentration of the viral inoculum and/or inoculation route. Interestingly, pulmonary disease with diffuse alveolar damage was previously documented in cats intratracheally infected with 1 × 10 6 TCID 50 SARS-CoV-1, which also resulted in efficient transmission of virus to uninfected animals [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%